2021
DOI: 10.3389/fphys.2021.623885
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Strength, Sprint, and Jump Performance in High-Level Female Football Players Are Maintained With a Customized Training Program During the COVID-19 Lockdown

Abstract: IntroductionThe COVID-19 outbreak with partial lockdown has inevitably led to an alteration in training routines for football players worldwide. Thus, coaches had to face with the novel challenge of minimizing the potential decline in fitness during this period of training disruption.MethodsIn this observational pre- to posttest study involving Norwegian female football players (18.8 ± 1.9 years, height 1.68 ± 0.4 m, mass 61.3 ± 3.7 kg), we investigated the effects of a prescribed home-based and group-based in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 36 publications
2
19
0
12
Order By: Relevance
“…On the other hand, Spyrou et al [ 23 ] did not observe significant differences in vertical jump after 70 days of quarantine in futsal elite players. These discrepancies in vertical jumping ability in students compared with athletes may be that athletes even in the case of lockdowns and quarantines were obliged to train at home [ 42 ]. In the present study we also observed that flexibility of lower back and hamstrings, measured by the sit-and-reach test, was significantly lower only in males after the 5-month lockdown compared with the previous cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Spyrou et al [ 23 ] did not observe significant differences in vertical jump after 70 days of quarantine in futsal elite players. These discrepancies in vertical jumping ability in students compared with athletes may be that athletes even in the case of lockdowns and quarantines were obliged to train at home [ 42 ]. In the present study we also observed that flexibility of lower back and hamstrings, measured by the sit-and-reach test, was significantly lower only in males after the 5-month lockdown compared with the previous cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Vier Studien [ 6 , 7 , 10 , 20 ] verglichen die Leistungsfähigkeit der Fußballspielenden mit Leistungsdaten aus vorherigen Spielzeiten. Zwei Studien [ 1 , 16 ] ermittelten die Leistungsfähigkeit der Sportler/-innen unmittelbar vor und nach der Lockdownperiode. Die Maßnahmen zur Eindämmung des Coronavirus variierten zwischen den Ländern und Regionen der einzelnen Studien und werden daher bei Erstnennung kurz erläutert.…”
Section: Ergebnisseunclassified
“… Squat Jumps und Counter Movement Jumps auf einer Kontaktplattform Sprunghöhe SJ (cm) Nordic-Hamstring-Curl mit Kraftaufnahme (exzentrische Kniebeuger) Messwerte der Kraftleistung: Sprint mittels Lichtschrankenmessung bei Start, 10 m und 20 m Absolute Kraft (N) Statistik: Relative Kraft (N/kg) t‑Test für verbundene Stichproben, Effektstärke Messwert der Sprintleistung: 10 m Sprintzeit (s; 6,9 % ) 20 m Sprintzeit (s; 4,3 % ) Pedersen et al. (2021) [ 16 ] 8 professionelle Fußballspielerinnen (Norwegen, Level 3) Dauer: 12 Wochen Design: Messwert der Kraftleistung: Alter: 18,8 ± 1,9 Jahre; Größe 168 ± 4 cm; Gewicht 61,3 ± 3,7 kg Wöchentliche Trainingszeit: 233 ± 47 min Prä- vs. Post-COVID-19 Einerwiederholungsmaximum (kg) Heimtraining: 4 Wochen Heimtraining Messwerte der Sprungleistung: Individuelles und kontaktloses Gruppentraining bestehend aus Kraft‑, Schnelligkeit‑, Sprung- und Laufübungen 8 Wochen kontaktloses Kleingruppentraining ohne Equipment Sprunghöhe (cm) Datenerhebung: Absprunggeschwindigkeit (ms) Kniebeugen Maximale und mittlere Kraft (N) Contermovement-Jumps auf Kraftmessplatte Maximale und mittlere Leistung (W) Sprint mittels Lichtschrankenmessung bei Start, 5 m, 10 m und 15 m Flugzeit (ms) Statistik: Messwert der Sprintleistung: t‑Test für verbundene Stichproben 5 m, 10 m & 15 m Sprintzeit (s) Cohen et al. (2020) [ 7 ] 16 professionelle Fußballspieler der 1. kolumbianischen Liga Dauer: 15 Wochen Design: Messwerte der Sprungleistung: Alter: 24,3 ± 3,8 Jahre; Größe: 179 ± 7 cm; Gewicht: 79,2 ± 9 kg Häufigkeit: 5‑ bis 6‑mal/Woche Prä- vs. Post-COVID-19-Quarantäne im Vergleich zu einer weiteren Prä-Post-Periode der Saisonp...…”
Section: Ergebnisseunclassified
See 1 more Smart Citation
“…These will include muscle strengthening, flexibility, neuromuscular control, balance and agility, core stability, plyometrics, sport-specific movements (of uttermost importance) and endurance in varying degrees according to the sport concerned. The balance between endurance or strength training and sport-specific training will have to be adapted as to compensate the reduced sport-specific training while maintaining overall fitness (Pedersen et al, 2021) (Balsalobre-Fernández et al, 2015Lim, 2020) and further development of these "tele-screening" approaches should be encouraged. Continuous monitoring of both training load and athlete wellbeing would be further recommended to individually tailor an optimal training.…”
Section: Sport-specific Risk Assessment and ≪Tele-prevention≫mentioning
confidence: 99%